Pendampingan UMKM dalam Peningkatan Pemasaran dan Standarisasi Produk Berbasis Prinsip Syariah di UD. Barokah Jaya Desa Kedungbanteng, Sukorejo, Ponorogo - Dwicahyo, Agung; Herlambang, Muhammad Giri; Muhammad, Ali Muhtar; Elsaputra, Agung Ramadhon; Dianto, Fauzi Fitrah; Sasongko, Yogi Banar (Universitas Pahlawan Tuanku Tambusai, 2025)
The mentoring program for Barokah Jaya Micro, Small, and Medium Enterprises (MSMEs) in optimizing marketing strategies and product weight standardization based on Sharia principles has had a significant impact on partners. This program aims to enhance business competitiveness, expand market reach, and ensure product standards align with Sharia principles. The methods used include training in Sharia-based digital marketing, assistance in social media utilization, and the implementation of a product weight standardization system. The results show that partners have successfully optimized Facebook as a marketing platform, contributing to increased sales. Additionally, the application of more accurate weight measurement methods has ensured product consistency in accordance with Islamic trade justice principles. The program's success was supported by the high commitment of partners and community support, while the main challenges included limited technology access and experience in digital marketing. To overcome these obstacles, additional hands-on mentoring sessions were conducted. With this success, it is expected that Barokah Jaya MSMEs can serve as a model for other businesses in implementing professional and sustainable Sharia-based business strategies.